Global Positioning System Monitoring of High-Risk Sex Offenders: Implementation Challenges and Lessons Learned. (December 2020) - Chamberlain, Alyssa W.; Smith, Sarah M.; Turner, Susan F.; Jannetta, Jesse
Agencies incorporating new technology inevitably face challenges in the implementation process. In response to the passage of Proposition 83, which mandated lifelong supervision of people convicted of sex offenses in California, San Diego County initiated a pilot program assessing Global Positioning System (GPS) monitoring of such offenders considered high risk for reoffending. Using interviews of parole agents and administrators, parole agent records of supervision, and GPS monitoring data, we assess the challenges and lessons learned from the program which help inform the current policy context of electronic monitoring. Results show that rigorous GPS supervision involves substantial workload and resource increases for parole agencies, and may not be appropriate for all individuals convicted of sex offenses. The ethical and legal challenges of electronic monitoring, more generally, require further attention. The future of GPS monitoring will depend on how programs are implemented and resources are managed, as well as how ethical issues are addressed.